Pengaruh Relationship Marketing terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Mediasi Sky Beauty Care Surabaya - Brigitta Cornelia Amanda; Wiwik Herawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of relationship marketing on customer loyalty with customer satisfaction as a mediating variable at Sky Beauty Care Surabaya. Relationship marketing, which encompasses aspects of trust, commitment, communication, and complaint handling, has been identified as an important strategy in building long-term relationships with customers. In this study, a quantitative approach was used with a survey method, where data was collected through questionnaires distributed to customers who have used Sky Beauty Care services. The analysis results show that relationship marketing has a significant effect on customer satisfaction. The trust built between customers and the company, the company's commitment to providing the best service, clear and open communication, and prompt and effective complaint handling all contribute to increased customer satisfaction. This high customer satisfaction, in turn, has a positive effect on customer loyalty. Customers who are satisfied with the service they receive are more likely to use the service again and recommend it to others, ultimately strengthening the customer's relationship with the company. These findings provide an important contribution to Sky Beauty Care in formulating more effective marketing strategies. Better implementation of relationship marketing can increase customer satisfaction and loyalty, which ultimately has a positive impact on business sustainability and growth. Therefore, companies need to continuously strengthen customer relationships by improving service quality, communicating effectively, and responding to customer complaints. Therefore, relationship marketing can be key to successfully retaining customers and increasing their loyalty. Furthermore, this study also shows that customer satisfaction is not only a direct result of relationship marketing but also a key driver in fostering sustainable customer loyalty.